THE ROLE OF GROWTH OPPORTUNITIES IN SHAPING CAPITAL STRUCTURE: A COMPARATIVE ANALYSIS OF REAL ESTATE COMPANIES - Yanuar Dananjaya; Hananiel Gunawan; Priskilla Napitupulu (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2025)
This study examines how growth opportunities influence capital structure decisions within the real estate sector through the lens of Trade-off and Pecking Order Theory. Using panel data from 58 publicly listed real estate companies (2019-2023), we investigate how growth opportunities affect the relationship between leverage and four determinants: profitability, liquidity, asset tangibility, and tax shield. By segmenting firms into high, medium, and low growth categories, our analysis reveals that profitability negatively affects leverage in both medium and high-growth firms, with stronger effects in high-growth firms, supporting Pecking Order Theory in environments of heightened information asymmetry. Asset tangibility shows a significant negative relationship exclusively in medium-growth firms, reflecting how inventory and land banks serve as potential collateral, though their effectiveness is dampened by information asymmetry in high and low-growth segments. Liquidity demonstrates a significant negative relationship in both high and medium-growth segments, with stronger effects in high-growth firms, while tax shield effects are insignificant across all categories. These findings contribute to capital structure literature by demonstrating how growth opportunities systematically alter traditional capital structure determinants in the real estate sector, offering important implications for corporate financial management.